Islamic corporate social responsibility (ICSR): validating a higher-order measurement model - Kamil, Naail Mohammed; Jan, Muhammad Tahir (Malaysian Institute of Management, 2014)
The present study investigates a higher-order measurement model of the Islamic corporate social responsibility (ICSR) construct in business organisations in the Malaysian context. The study aims to contribute new knowledge to the existing literature of corporate social responsibility (CSR) in general, and Islamic CSR in particular. Using disproportionate stratified random sampling, the survey data used for this empirical research were drawn from 219 Muslim managers in business organizations in Malaysia. After yielding an instrument to measure ICSR, a principal component analysis (PCA) and a confirmatory factor analysis (CFA) were conducted. Good fit indices from the CFA revealed that the higher-order ICSR measurement model in the Malaysian business context is explained by four components: integrity, fulfilment of covenants, justice, and truthfulness. The study’s theoretical and practical implications were also discussed.